Production of succinic acid from eucalyptus kraft pulp hydrolysates - Macedo, Alfredo Pina de (2022)
Succinic acid is an important “building block” to the chemical and polymer industries, being the base molecule for the synthesis of a vast array of products. Despite its biological origin, the succinic acid was initially produced by the petrochemical industry, having high environmental impacts like the release of CO2. Nowadays, with the increasing development of biotechnology and due to environmental and economic concerns, there is a significant production of succinic acid by bioprocesses, within the biobased industry. The biological production of succinic acid includes the consumption of CO2 and contributes for reducing the emissions. Moreover, it is well documented the possibility of using agro-industrial wastes such as lignocellulosic, as feedstocks to produce succinic acid. From those it is possible to evidence the residues originated by the pulp and paper industry, namely wood residues, for which the kraft process could be used as a pre-treatment candidate for bioprocesses. The aim of this work was to produce succinic acid from cellulose pulp obtained by delignification of Eucalyptus globulus wood through kraft cooking. The first step was an enzymatic hydrolysis of the celluloses and hemicelluloses to produce a hydrolysate composed by the respective monosaccharides. This hydrolysate was fermented by the bacterium Actinobacillus succinogenes, the process biocatalyst operated under batch and fed-batch conditions. Using the kraft wood pulp hydrolysate, it was possible to attain a succinic acid concentration of 19.93 g/L, with a yield and productivity of 0.399 g/L.h and 0.331 gsuccinic acid/gsugars, respectively. These values were improved with the addition of magnesium carbonate, however, this salt also led to the production of a higher concentration of byproducts. In the fed-batch fermentation, it was verified that the lactic acid production surpassed the succinic acid production. Nonetheless, those results further evidenced the possibility of exploiting this fed-batch operation to produce both succinic and lactic acid. This study served as a reference for future studies fed with wood residues, in order to their integration into a pulp and paper biorefinery working according to the Circular Economy model.